Principles of School-Based Educational Management at SMK Negeri 6 Manado - Mewengkang, Christie Garry; Mulalinda, Ryanthi; Tamasintang, Findy; Caroles, Neila (Peneliti.net, 2024)
School-Based Management (SBM) is an educational management approach that grants schools greater autonomy to manage resources and educational processes independently and transparently. At SMK Negeri 6 Manado, SBM principles such as transparency, independence, partnership, participation, and accountability are applied to enhance educational quality and strengthen community relationships. This study employs a qualitative method through observation and interviews with school stakeholders. The findings reveal that SMK Negeri 6 Manado has successfully utilized SBM principles to address various challenges, including managing the salaries of honorary teachers through community participation. Additionally, collaboration between the school, community, and industrial sectors provides students with direct experience in entering the workforce. However, challenges persist in managing BOS funds, which can no longer be used to pay honorary teachers' salaries. The implementation of SBM at SMK Negeri 6 Manado demonstrates that this approach can support inclusive, relevant, and community-based collaborative education.